(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Malykhina S. V. Conceptual and categorical analysis of the essential understanding the didactic intensification of students’ educational activities. The article covers the main aspects of conceptual and categorical analysis of essential understanding the didactic intensification of students’ educational activities. The author summarizes approaches towards defining basic concepts and categories. The author’s conceptual and categorical understanding the didactic intensification of students’ educational activities relies on organizational and pedagogical, praxeological and objective or analytical and prognostic reasons.